The Effectiveness of the Integrated BBT Method (Read-Tiered-Structured) in Improving Reading Literacy among Elementary School Students: A Quasi-Experimental Study - Gracianus Edwin Tue P. Lejap; Hildegardis Missa; Madar Alexius; Maria Aloisia Uron Leba (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study aims to evaluate the effectiveness of the Integrated BBT Method (Reading-Tiered-Structured) in improving elementary school students’ reading literacy. The research employed a quantitative, quasi-experimental one-group pre-test–post-test design involving 56 students from Grades I–VI at SD Inpres Bone, South Central Timor Regency, East Nusa Tenggara, using a saturated sampling technique. The intervention was implemented over four weeks in sequential stages: reading letters, words, sentences, and paragraphs. The research instrument consisted of a reading literacy test developed by the Ministry of Education, Culture, Research, and Technology (Kemdikbudristek), and data were analyzed using a paired-samples t-test. The results indicated a significant improvement in reading literacy, with a significance value (2-tailed) of 0.000 (< 0.05). The t-values across the five levels were -18.044, -37.293, -30.529, -15.152, and -13.550, respectively, with 55 degrees of freedom. The effect size values at the five levels were 3.151571, 6.721453, 5.412058, 2.563162, and 2.281976, respectively, with average post-test achievement exceeding 97% across all levels. The limitations of this study include the absence of a control group and the short duration of the intervention. Theoretically, these findings strengthen the effectiveness of a staged literacy approach, while practically, they provide an applicable model for reading instruction. This study recommends implementing the Integrated BBT Method to strengthen reading literacy policy in Indonesian elementary schools. Keywords: elementary school students, integrated BBT method, quasi-experimental study, reading literacy